ANALISIS PERBANDINGAN BIAYA DAN WAKTU PEKERJAAN PELAT BETON KONVENSIONAL DENGAN PANEL BETON - Maskur, Atep; Ramdan, Sahrul; Setiari , Idan (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2022)
The New Classroom of Galuh University is a 2-storey building that uses concrete floor panel slab construction. The use of the concrete floor panel slabs is due to insufficient road access to the location to use ready mix cast concrete and to streamline project implementation time. The purpose of this study is to find out how much the cost and time comparison of the work of conventional concrete floor slabs and concrete floor panels is. This research was conducted in the new classroom building of Galuh University. The results of data analysis show that the budget required for conventional concrete floor slab work in Galuh University's New Classroom Building is Rp. 368,160,000.00,- with the price for 1 m3 is Rp. 4,613,524.65,-. And the budget needed for the floor panel slab work on the Galuh University New Classroom Building is Rp. 359,100,000.00,- with the price for 1 m3 is Rp. 4,500,000,000.00,-. Based on the price comparison, concrete floor slabs are about 2.46% more efficient than conventional concrete slabs. This is because there is a price difference of Rp. 9,060,000.00,-. The work time needed to complete the Conventional Floor Plate work is 27 days and the work time needed to complete the Floor Panel Plate work is 21 Days. Based on the comparison of work time, Floor panel plates are 22.22% more efficient for work time.